2020
DOI: 10.1186/s13756-020-00729-2
|View full text |Cite
|
Sign up to set email alerts
|

Early discontinuation of empirical antibiotic treatment in neutropenic patients with acute myeloid leukaemia and high-risk myelodysplastic syndrome

Abstract: Introduction: Current guidelines advocate empirical antibiotic treatment (EAT) in haematological patients with febrile neutropenia. However, the optimal duration of EAT is unknown. In 2011, we have introduced a protocol, promoting discontinuation of carbapenems as EAT after 3 days in most patients and discouraging the standard use of vancomycin. This study assesses the effect of introducing this protocol on carbapenem and vancomycin use in high-risk haematological patients and its safety. Methods: A retrospect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 15 publications
(28 reference statements)
1
15
0
Order By: Relevance
“…Implementation of ECIL-4 recommendations reduced the number of days on antibiotic therapy by a median of 2 days relative to a 27-day median duration of hospitalization, in line with previously published studies [ 9–11 , 14 , 17 ]. To account for the effect of combination therapy, we calculated total antibiotic exposure, which was more extensively reduced by a median of 7 daily doses.…”
Section: Discussionsupporting
confidence: 87%
“…Implementation of ECIL-4 recommendations reduced the number of days on antibiotic therapy by a median of 2 days relative to a 27-day median duration of hospitalization, in line with previously published studies [ 9–11 , 14 , 17 ]. To account for the effect of combination therapy, we calculated total antibiotic exposure, which was more extensively reduced by a median of 7 daily doses.…”
Section: Discussionsupporting
confidence: 87%
“…Most published studies are retrospective or prospective observational, and the de-escalation and continuation arms are often not well matched (Table 1). Within the limitations of these studies, most found similar outcomes including rates of ICU admission and mortality in the de-escalation arm to the continuing antibiotic arm [61,62,[77][78][79][80][81]. Some reduction in carbapenems and vancomycin use has also been shown [77,79].…”
Section: Early De-escalation Of Therapy To Fluoroquinolone Prophylaxi...mentioning
confidence: 86%
“…Within the limitations of these studies, most found similar outcomes including rates of ICU admission and mortality in the de-escalation arm to the continuing antibiotic arm [61,62,[77][78][79][80][81]. Some reduction in carbapenems and vancomycin use has also been shown [77,79].…”
Section: Early De-escalation Of Therapy To Fluoroquinolone Prophylaxi...mentioning
confidence: 86%
“…These studies further demonstrate that implementation of ECIL guidelines in high-risk neutropenic patients was safe and feasible. Several of these studies demonstrated a significant reduction in BSA use, yet no differences in ICU transfers, bacteremia incidence, infection relapses, or mortality [29–32]. While two studies observed a higher bacteremia incidence in patients that followed ECIL-guidelines [33 ▪ ,34], two also showed a decreased risk of ICU [35 ▪ ] admission and death [34,35 ▪ ].…”
Section: When Can We De-escalate or Stop Antibiotics?mentioning
confidence: 99%